Exposure of RC building structures to the marine environment of the Valencia coast. (January 2018) - Moreno, Jose D.; Pellicer, Teresa M.; Adam, Jose M.; Bonilla, Mercedes
Abstract: As the marine atmosphere is very harmful to reinforced concrete (RC) structures, buildings situated close to the sea are at a high risk of suffering damage. Such is the case for many of the buildings near the coast in Valencia (Spain). Most of these buildings were built between 1968 and 2007, and nowadays their RC structures are seriously damaged. This paper describes the condition of 1816 buildings that were inspected in 14 towns along the Valencia coast. From these inspections, there have been identified the main factors which are the most significant in the damage of these RC structures by the aggressive marine conditions. These factors include environmental characteristics, urban parameters, and the construction system of the buildings. Highlights: Marine atmosphere is very harmful to reinforced concrete (RC) structures. 1816 buildings were inspected in 14 towns placed in Valencia coast (Spain). The main factors affecting RC structures in aggressive marine conditions are analysed. These factors include environmental characteristics, urban parameters and construction methods.